A bench‐scale study of potable reuse impacts on surface water treatment. Issue 5 (11th October 2020) - Adelman, Michael J.; Smith, Mia S.; Hancock, Tony D.; Borchardt, James H.; Williams, Michael D.; Quicho, Joseph; Weber‐Shirk, Monroe L.
Abstract: Water utilities are considering raw water augmentation schemes to blend potable reuse water directly into the raw water for existing water treatment plants (WTPs). In this study, bench‐scale testing evaluated the impacts of introducing advanced‐treated reuse water (treated by ozonation, biological active carbon, ultrafiltration, reverse osmosis, and advanced oxidation) into the raw water supply of an existing WTP. To determine whether treatment would remain effective, blends of raw water and reuse water were coagulated, flocculated, and settled in a jar test apparatus matching the flocculator energy dissipation rate of the full‐scale WTP and were tested for filterability, defined as positive removal of turbidity through 5‐μm filter paper. The testing demonstrated that blends were treatable across a range of conditions, and alkalinity was the main observed limitation for treatability. Conditioning the advanced‐treated reuse water to add both hardness and alkalinity buffered against extreme pH drops during coagulation. This also achieved pH and calcium carbonate indexes after treatment that matched the current finished water, but some stability indexes shifted in a more corrosive direction, suggesting a topic for future research. Overall, this study demonstrated that the coagulation, flocculation, settling, and filtration processes of an existing WTP can treat potable reuse blends provided alkalinity is sufficient, and this is an important finding for the viability of raw water augmentation.